Effects of Storage Condition and Time on the Microbiological Attributes of some Stored Yoghurts Marketed in Enugu Metropolis (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
This study comparatively investigated the effects of storage condition and time on the  microbiological qualities  of some stored yoghurts marketed in the Enugu metropolis. The experiment was  factorial (2x6x4) involving a completely randomized design (CRD). A total of 96 samples comprising four samples of yoghurt coded A, B, C and D were sourced from different producers and designated as A – Food Science and Technology lab (FST), B – Aqua Rapha yoghurt, C – Chariot yoghurt and D – A.S yoghurt samples. The samples were stored for a period of seventy days under two storage conditions – refrigerated (50C) and room  temperatures (28±20C). All samples were analyzed for microbiological parameters such as total viable count (cfu), coliform (cfu),  fungal/yeast (cfu) . Statistical analysis was conducted using two-way ANOVA to determine the mean differences. The results  showed that total viable count, coliform  count, yeast /fungal counts  increased  with  storage  time but the  rate of increase was significantly higher(